The Burden of Coronavirus Disease 2019–Related Cases, Hospitalizations, and Mortality Based on Vaccination Status and Mandated Mask Use: Statewide Data From Wisconsin and Narrative Review of the Literature. (18th February 2022) - Abd-Elsayed, Alaa; D'Souza, Ryan S.
Abstract : BACKGROUND: Coronavirus disease 2019 (COVID-19) cases continue to surge in the United States with the emergence of new variants. Statewide variability and inconsistency in implementing risk mitigation strategies are widespread, particularly in regards to enforcing mask mandates and encouraging the public to become fully vaccinated. METHODS: This is a cross-sectional study conducted on July 31, 2021, utilizing publicly available data from the Wisconsin Department of Health Services. The authors abstracted data on total COVID-19–related cases, hospitalizations, and deaths in the state of Wisconsin. The primary objective was comparison of total COVID-19–related cases, hospitalizations, and deaths in vaccinated versus unvaccinated people in the state of Wisconsin over a 31-day period (July 2021). Furthermore, we also performed a narrative review of the literature on COVID-19–related outcomes based on mask use and vaccination status. RESULTS: In the state of Wisconsin during July 2021, total COVID-19 cases was 125.4 per 100, 000 fully vaccinated people versus 369.2 per 100, 000 not fully vaccinated people (odds ratio [OR] = 0.34, 95% confidence interval [CI], 0.33–0.35; P < .001). Total COVID-19 hospitalizations was 4.9 per 100, 000 fully vaccinated people versus 18.2 per 100, 000 not fully vaccinated people (OR = 0.27, 98% CI, 0.22–0.32; P < .001). Total COVID-19 deaths was 0.1 per 100, 000 fully vaccinated people versus 1.1 per 100, 000 not fully vaccinated people (OR = 0.09, 95% CI, 0.03–0.29; P < .001). Narrative review of the literature demonstrated high vaccine effectiveness against COVID-19 infection prevention (79%–100% among fully vaccinated people), COVID-19–related hospitalization (87%–98% among fully vaccinated people), and COVID-19–related death (96.7%–98% among fully vaccinated people). Studies have also generally reported that mask use was associated with increased effectiveness in preventing COVID-19 infection ≤70%. CONCLUSIONS: Strict adherence to public mask use and fully vaccinated status are associated with improved COVID-19–related outcomes and can mitigate the spread, morbidity, and mortality of COVID-19. Anesthesiologists and intensivists should adhere to evidence-based guidelines in their approach and management of patients to help mitigate spread.